Exegetical checkmate – Isaiah 4:2a: person or plant? - Kruger, H (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
Traditionally interpreters have understood the phrase HWHY JMIX, in Isaiah 4:2a as an indication of a messianic figure and translated it as “Shoot of the Lord”. To highlight this meaning the word concerned was written with a capital letter. Presently however, in stead of translating the expression with reference to a person, and particularly a messianic figure, several scholars prefer to interpret the phrase as a portrayal of luxuriant vegetation. The study reconsiders the case in terms of some aspects of inner- and inter-textual exegesis.